2008
DOI: 10.1177/1545109708328130
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Health Literacy and HIV Treatment Adherence: Further Evidence from Objectively Measured Medication Adherence

Abstract: Background People with lower health literacy are vulnerable to health problems. Studies that have examined the association between literacy and medication adherence have relied on self-reported adherence, which is subject to memory errors, perhaps even more so in people with poor literacy. Purpose To examine the association between health literacy and objectively assessed HIV treatment adherence. Methods Men and women (N = 145) receiving antiretroviral therapies completed a test of health literacy and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 29 publications
6
90
2
2
Order By: Relevance
“…This is justified by the fact that health literacy is a subjective aspect of the human being, which is more convenient to evaluate by such studies. However, there are few studies on health literacy in the context of people living with HIV/Aids, a fact evidenced by this research, (24) . (25) .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This is justified by the fact that health literacy is a subjective aspect of the human being, which is more convenient to evaluate by such studies. However, there are few studies on health literacy in the context of people living with HIV/Aids, a fact evidenced by this research, (24) . (25) .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the use of educational technologies is a current trend that improves patients' knowledge about the Health literacy for people living with HIV/Aids: an integrative review Cunha GH, et al conduct of the treatment, but should be used with caution, especially considering the patient access to different types of existing technologies (15)(16)(17)(18) . It is also noteworthy that in areas of extreme poverty, a larger number of behavioral and clinical educational interventions is required to achieve and maintain optimal levels of adherence, and virologic suppression successful long-term treatment (15,(23)(24)(25) .…”
Section: Chart 3 (Concluded)mentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed, the literature shows that SCD patients' ability to find, understand and utilize health information may be diminished before and after transition; and, when health literacy is low, poor health outcomes follow (Kalichman et al, 2008;Kutner et al, 2006).…”
Section: Factors Influencing Transitionmentioning
confidence: 99%
“…421 In fact, a cross-sectional study aimed at examining the association between health literacy and objectively assessed HIV treatment adherence found the relation between these two dimensions to be robust, with health literacy predicting adherence over and above all other factors. 75 As well, through multivariate regression models examining the associations among race, literacy, and HIV-medication adherence in a convenience sample of HIV infected patients recruited from two different clinics, Osborn and colleagues 76 found that health literacy mediated the relationship between race and poor HIV-medication adherence, performing as a significant independent predictor of nonadherence. Waldrop-Valverde et al 77 expanded these findings, suggesting that health literacy skills -especially functional ones -mediated the impacts of gender on the appropriate medication management of HIV.…”
Section: The Drawbacks Of Poor Health Literacy On Hiv Treatmentmentioning
confidence: 99%